Cooperation and Competition in the Innovation Ecosystem From the Perspective of Evolutionary Psychology - Zhao, Xiaochun (Frontiers in Psychology, 2021)
The innovation ecosystem is distinct from innovation itself; the former is based on technology, talent, and markets, as well as many other elements of innovation that form the organisational system. Current research on the innovation ecosystem has primarily focused on theoretical discussions of the concept and analysis of evolution mechanisms and influential factors; however, research on mechanisms that influence cooperation and competition within the system is limited. Corporation and competition are the critical elements in the acquisition value of the innovation ecosystem and the realisation of innovation breakthroughs. Given the dynamic nature and complexity of the innovation ecosystem, our research is based on the "value co-creation" theory of innovation ecosystems and consistency with the "reciprocity" principle of evolutionary psychology. Understanding the mechanisms that underlie corporation and competition in the innovation ecosystem from the perspective of evolutionary psychology may foster more efficient cooperation and competition among enterprises, enabling them to realise the value of co-creation and innovation breakthroughs.